2020
DOI: 10.1111/cyt.12803
|View full text |Cite
|
Sign up to set email alerts
|

An audit of liquid‐based cytology samples reported as high‐risk human papillomavirus and borderline nuclear change in endocervical cells

Abstract: Introduction Primary human papillomavirus (HPV) screening, testing for the virus responsible for 99% of cervical cancers, was introduced in 2018‐2020 in the UK. This was preceded by HPV triage of low‐grade cytology from 2012. Much of the evidence incorporated into current National Health Service (NHS) colposcopy guidance assessed outcomes prior to this change in screening. The aim of this paper is to assess adherence to NHS cervical screening programme standards, determine the incidence of cases reported as hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Specifically, a metaanalysis regarding borderline cytology on cervical samples by Schnatz et al 17 19 One audit of 22 women referred with borderline changes in endocervical cells and positive high-risk HPV revealed AIS in seven patients and high-grade CIN in eight. 20 One recent study of referrals with borderline changes in liquid-based cytology without assessment of high-risk HPV described outcomes of 4.3% and 7.2% for AIS and malignancy, respectively, with the percentage of invasive adenocarcinoma being 4.3%. 21 A similar study 22 revealed the presence of borderline referral cytology in 18% of the patients with pre-invasive or invasive cervical adenocarcinoma, with 52% of the total number of patients having low-grade or negative cytology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, a metaanalysis regarding borderline cytology on cervical samples by Schnatz et al 17 19 One audit of 22 women referred with borderline changes in endocervical cells and positive high-risk HPV revealed AIS in seven patients and high-grade CIN in eight. 20 One recent study of referrals with borderline changes in liquid-based cytology without assessment of high-risk HPV described outcomes of 4.3% and 7.2% for AIS and malignancy, respectively, with the percentage of invasive adenocarcinoma being 4.3%. 21 A similar study 22 revealed the presence of borderline referral cytology in 18% of the patients with pre-invasive or invasive cervical adenocarcinoma, with 52% of the total number of patients having low-grade or negative cytology.…”
Section: Discussionmentioning
confidence: 99%
“…The first study in the UK that documented outcomes of referrals with borderline changes of squamous cells on cytology in combination with a high‐risk HPV positive test was the Sentinel Sites study, which showed 15.7% having high‐grade CIN, including three cases of invasive cancers, in 3161 patients 19 . One audit of 22 women referred with borderline changes in endocervical cells and positive high‐risk HPV revealed AIS in seven patients and high‐grade CIN in eight 20 . One recent study of referrals with borderline changes in liquid‐based cytology without assessment of high‐risk HPV described outcomes of 4.3% and 7.2% for AIS and malignancy, respectively, with the percentage of invasive adenocarcinoma being 4.3% 21 .…”
Section: Discussionmentioning
confidence: 99%